2003
DOI: 10.2466/pms.2003.97.3f.1307
|View full text |Cite
|
Sign up to set email alerts
|

Conspicuous Histomorphological Anomalies in the Hippocampal Formation of Rats Exposed Prenatally to a Complex Sequenced Magnetic Field within the Nanotesla Range

Abstract: The brains of adult rats, exposed prenatally to one of four intensities (between 10 nanoTesla and 1.2 microTesla) of either a frequency-modulated magnetic field or a complex sequenced field designed to affect brain development, were examined histologically. Although from each intensity some rats that had been exposed to the complex sequenced magnetic field showed minor anomalies, those exposed to intensities between 30 nT and 180 nT exhibited conspicuous anomalous organizations of cells within the hippocampal … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
12
0

Year Published

2007
2007
2012
2012

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 10 publications
(14 citation statements)
references
References 11 publications
2
12
0
Order By: Relevance
“…While the 7 Hz waveform has been used in several experiments (Cook and Persinger, 2000; Persinger et al, 2000; Kinoshameg and Persinger, 2004), this is the first investigation into any developmental effects from exposure. Here, perinatal exposure to the field significantly impacted motor behaviour in a manner consistent with previous studies which used intensities many times greater (Persinger, 1969; St. Pierre and Persinger, 2003; McKay et al, 2003a,b). The effects seen here were pronounced at the higher intensities as the 50 and 500 nT‐exposed rats exhibited dramatic increases in movement and bodyweight.…”
Section: Discussionsupporting
confidence: 88%
“…While the 7 Hz waveform has been used in several experiments (Cook and Persinger, 2000; Persinger et al, 2000; Kinoshameg and Persinger, 2004), this is the first investigation into any developmental effects from exposure. Here, perinatal exposure to the field significantly impacted motor behaviour in a manner consistent with previous studies which used intensities many times greater (Persinger, 1969; St. Pierre and Persinger, 2003; McKay et al, 2003a,b). The effects seen here were pronounced at the higher intensities as the 50 and 500 nT‐exposed rats exhibited dramatic increases in movement and bodyweight.…”
Section: Discussionsupporting
confidence: 88%
“…These anomalies occurred in the same region associated adult neuronal neurogenesis due to seizures in rats (Scharman et al 2000) and temporal lobe epileptic patients (Mathern et al 1995). In another experiment St-Pierre and Persinger (2003) found a massive collection of heterotypic cells, arranged as rosettes with normally shaped neurons, extending across the entire coronal area of the right hippocampus within the CA3-hilar region of one of the rats exposed to the low intensity complex sequence field.…”
Section: Discussionmentioning
confidence: 85%
“…The temporal structures of the complex magnetic fields used in this study (composite, LTP‐like, and non‐sinusoidal 50 Hz) have shown empirical effectiveness in influencing brain development and behavior when individually applied (Persinger and Koren, 2007; St‐Pierre et al, 2008; St‐Pierre and Persinger, 2003, 2008; Whissell et al, 2009). In summary, the composite pattern was composed of 40, 250 ms signatures that involved various frequency‐modulated patterns as well as those derived from mathematical relationships (Persinger, 2010; Persinger and Koren, 2007).…”
Section: Methodsmentioning
confidence: 96%